MODEL PENDIDIKAN BERBASIS KHALIFAH FIL ARDH DI SPMAA: INTEGRASI EKOLOGI ISLAM DAN KEMANDIRIAN EKONOMI SEBAGAI FONDASI PERADABAN BERKELANJUTAN - Thooriq Nur Hidayat; Naufal Nadhif Hibatullah (Journal of Social and Economics Research, 2026)
This research aims to analyze the Khalifah fil Ardh-based education model at SPMAA Lamongan Islamic Boarding School as an integrative solution to the ecological crisis and economic dependence of Islamic educational institutions. Utilizing a qualitative method with a case study approach, data were collected through participatory observation and in-depth interviews with practitioners. The results show that SPMAA has successfully translated the theology of vicegerency (khalifah) into concrete managerial practices through three main instruments: 1) Spiritual HR management based on the Tenaga Penyayang Umat (TPU) philosophy and the Pegawai Gaji Akherat (PGA) work ethos, which creates extreme operational efficiency; 2) Radical financial independence through a "no proposal" policy that maintains institutional integrity; and 3) The implementation of Ecopesantren through a circular organic farming system that builds food sovereignty. This study concludes that the integration of ritual piety with ecological-economic piety is the key to creating a sustainable Islamic civilization. This model offers a new paradigm for Islamic education to return to its roots of independence in facing global crisis challenges.